The place of racism and racial discrimination in the memories of the Afro-education - Maria Isabel Mena Garcia (Universidade Federal de Santa Catarina, 2019)
The article presents the results of a research carried out with teachers of educational institutions in Bogotá, which aimed to measure some perceptions about racism and racial discrimination and its incidence in the development and implementation of the Chair of Afro-Colombian Studies (CEA). The study makes it clear that the Chair does not take place within the Institutional Educational Project in its pedagogical, administrative and community development components, despite 18 years since its regulation in Colombia.